Actin-like protein 8, a member of cancer/testis antigens, supports the aggressive development of oral squamous cell carcinoma cells via activating cell cycle signaling. (April 2022) - Wang, Lifang; Xing, Xiaoling; Tian, Hua; Fan, Qingchun
Highlights: ACTL8 is up-regulated in OSCC tissues and cell lines. Knockdown of ACTL8 inhibits the growth and mobility of OSCC cells. There is a significant correlation between ACTL8 expression and tumor status. ACTL8 expression is negatively associated with OSCC prognosis. Abstract: Due to the malignancy of oral squamous cell carcinoma (OSCC), investigations of novel therapeutic targets and prognostic biomarkers are urgently needed. In our present study, significant up-regulation of Actin-like protein 8 (ACTL8) in OSCC patients was observed by bioinformatics analysis with RNA sequencing data obtained from The Cancer Genome Atlas (TCGA) database. The results of Chi-square test revealed that there was a significant correlation between ACTL8 expression and tumor status (T1 + T2/T3+T4) (P = 0.004). Survival analysis indicated a negative correlation between ACTL8 overexpression and prognosis in OSCC (P = 3.984e-02). An ACTL8 knockdown experiment was conducted to evaluate the function of ACTL8 on OSCC cell biological behaviors. The results revealed that knockdown of ACTL8 significantly inhibited the growth and mobility, arrested cell cycle and promoted apoptosis of TCA-83 and CAL27 cells. Moreover, Gene Set Enrichment Analysis (GSEA) and western blots demonstrated that activation of cell cycle signaling pathway was inhibited by knockdown of ACTL8, as we observed the down-regulation of 4 key proteins (CDK1, cyclin E1, cyclin B2 and c-Myc) in this pathway. The present investigation indicates that ACTL8 plays an oncogenic role in the pathogenesis of OSCC, suggesting that ACTL8 may be a promising therapeutic target and prognosis marker for human OSCC.